High-purity low-thermal-conductivity low-density carbon fiber / carbon composite thermal field material and preparation method thereof

Through high-speed shear dry dispersion and rotary pressing curing technology, combined with high-temperature carbonization and graphitization and high-temperature chemical purification, a high-purity, low-thermal conduction and low-density carbon fiber/carbon composite heat field material was successfully prepared, solving multiple problems in the preparation process and application of existing materials, and achieving improvement in material performance and production efficiency.

CN119822863AActive Publication Date: 2025-04-15HANGZHOU KAIKEN NEW MATERIAL TECH CO LTD
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
CN202510308056.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-15
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

In the preparation process and actual application of existing low-density chopped carbon fiber/carbon composites, there are problems such as uneven material dispersion, inconsistent performance, low production efficiency, large energy consumption, serious environmental pollution, and lack of performance testing and evaluation methods.

Method used

The powdered resin and chopped carbon fiber were dispersed by high-speed shear dry method, cured by rotary pressing and heating, combined with high-temperature carbonization and graphitization, and finally high-temperature chemical purification was performed using a mixed powder of chlorinated polyvinyl chloride and polytetrafluoroethylene.

Benefits of technology

A high-purity, low thermal conductivity, low thermal conductivity, low thermal conductivity, low thermal conductivity, low thermal conductivity, and low conductivity are achieved, which solves the problems of inconsistent material performance, low production efficiency, large energy consumption and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822863A_ABST
    Figure CN119822863A_ABST
Patent Text Reader

Abstract

The invention provides a high-purity low-thermal-conductivity low-density carbon fiber / carbon composite thermal field material and a preparation method thereof. The preparation method is high in production efficiency, low in energy consumption and small in pollution, the preparation process is simple and rapid, and the finally prepared low-density carbon fiber / carbon composite thermal field material has the excellent performance of being uniform in fiber material distribution, low in density, resistant to high temperature, low in heat conductivity coefficient, high in purity, low in conductivity and the like. The density of the composite thermal field material is less than or equal to 0.2 + / -0.01 g / cm; the content of impurity elements is less than or equal to 17ppm; and the conductivity is less than or equal to 5.7 S / cm. The heat conductivity coefficient at 1500 DEG C is less than or equal to 0.46 W / (m.K); and the power at 2300 DEG C in a 6-inch silicon carbide crystal growth furnace is less than or equal to 14.8 kW.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-purity, low-thermal-conductivity, low-density carbon fiber / carbon composite thermal field materials for semiconductor industry, and in particular to a high-purity, low-thermal-conductivity, low-density carbon fiber / carbon composite thermal field material and a preparation method thereof. Background Art

[0002] Low-density carbon fiber / carbon composite materials (density less than 0.5 g / cm³) are widely used in high-temperature thermal insulation materials due to their excellent high-temperature resistance (1500-3000℃, in vacuum or protective gas) and low thermal conductivity (thermal conductivity less than 0.5 W / (mK)), including single crystal silicon, polycrystalline silicon, silicon carbide crystal growth, silicon carbide epitaxial growth, sapphire crystal growth, optical fiber rod making and stretching, and high-temperature heat treatment of metals. Such materials are usually made of carbon fibers (such as PAN-based, viscose-based, asphalt-based) and resins (such as phenolic resins, asphalt) as raw materials, and are prepared through processes such as impregnation, curing, carbonization, graphitization, and purification.

[0003] At present, low-density carbon fiber / carbon composites are mainly divided into two categories: low-density long carbon fiber / carbon composites (carbon fiber length is at the centimeter level) and low-density chopped carbon fiber / carbon composites (carbon fiber length is at the millimeter level).

[0004] Classification and characteristics of existing technologies Low-density long carbon fiber / carbon composite material: The carbon fibers are mainly distributed in the XY plane, with fewer fibers in the Z direction, forming an anisotropic structure and presenting a three-dimensional layered network structure.

[0005] Preparation process: Carbon fiber felt (made of long carbon fiber, white silk or pre-oxidized silk) is impregnated with phenolic resin in liquid phase, cured and formed, and then subjected to high-temperature carbonization and graphitization.

[0006] Advantages: It has good thermal insulation performance and is suitable for resistance furnace heating furnace.

[0007] Disadvantages: Because carbon fibers are long, they are easy to form a continuous conductive network with high conductivity, and are easy to produce induction self-heating in the electromagnetic induction furnace, so they are not suitable for electromagnetic induction furnaces.

[0008] Low density chopped carbon fiber / carbon composite materials: The short-cut carbon fibers (e.g., 3-5 mm in length) are compounded with resin and prepared through impregnation, curing, carbonization and graphitization processes.

[0009] Since the anisotropy of chopped carbon fiber is low and closer to an isotropic structure, the thermal conductivity is relatively high, but the electrical conductivity is low and it is not easy to be heated by electromagnetic induction, so it is more suitable for use in electromagnetic induction heating furnaces.

[0010] Electromagnetic induction furnaces have a faster heating rate than resistance heating furnaces and can more easily reach high temperatures above 2000°C. Therefore, many semiconductor crystal growth furnaces and epitaxial growth furnaces currently use low-density chopped carbon fiber / carbon composite materials as thermal field insulation materials.

[0011] Problems with existing technologies Although low-density chopped carbon fiber / carbon composite materials have certain application advantages in electromagnetic induction furnaces, there are still the following problems in their preparation process and practical application: Material dispersion uniformity problem: Existing preparation methods mostly use liquid phase impregnation-molding curing process. Due to poor interface bonding, the resin cannot evenly coat the carbon fiber, resulting in uneven impregnation. During the curing process, the resin may slide to the bottom due to gravity, or the external mold temperature is high, resulting in external resin accumulation and less internal resin, resulting in uneven density above and below, and uneven density inside and outside. This unevenness leads to inconsistent mechanical strength and thermal conductivity of the final composite material, which brings problems to practical applications.

[0012] Efficiency, energy and environmental issues: The large amount of solvent used in the liquid phase impregnation process not only increases the environmental burden, but also leads to high energy consumption in the solvent removal process. The addition and removal of solvents prolongs the process time and reduces production efficiency.

[0013] Thermal conductivity evaluation questions: Chopped carbon fiber / carbon composite materials are usually used in high-temperature environments above 1000°C or even 2000°C, but there are currently few means of evaluating the actual use of such materials, making it difficult to accurately measure their actual performance.

[0014] In summary, existing low-density chopped carbon fiber / carbon composite materials have problems such as uneven material dispersion, inconsistent performance, low production efficiency, high energy consumption, serious environmental pollution, and lack of performance testing and evaluation methods. Therefore, material structure design, preparation methods and evaluation methods are in urgent need of improvement and innovation. Summary of the invention

[0015] The object of the present invention is to provide a method for preparing a high-purity, low-thermal-conductivity, low-density carbon fiber / carbon composite thermal field material with high production efficiency, low energy consumption, low pollution, and simple and fast preparation process.

[0016] Another object is to provide a high-purity, low-thermal-conductivity, low-density carbon fiber / carbon composite thermal field material with uniform fiber material distribution, low density, high temperature resistance, low thermal conductivity, high purity and low electrical conductivity.

[0017] The technical solution of the present invention: A high-purity, low-thermal-conductivity, low-density carbon fiber / carbon composite thermal field material, which has the following characteristics: Density: ≤0.2±0.01 g / cm³; Impurity element content: ≤17ppm; Conductivity: ≤5.7 S / cm.

[0018] In addition, the material has the following properties: 1500℃ thermal conductivity: ≤0.46 W / (m·K); Power in a 6-inch SiC crystal growth furnace at 2300°C: ≤14.8 kW.

[0019] The present invention also discloses a method for preparing a high-purity, low-thermal-conductivity, low-density carbon fiber / carbon composite thermal field material, the preparation method comprising the following steps: Step 1: Dispersing the powdered resin material and the chopped carbon fiber by high-speed shear dry method; Step 2: Heating and curing by rotation pressing; Step 3: After fixing with carbon fiber cloth and high-density perforated carbon fiber / carbon composite material sheet, high-temperature carbonization and graphitization are performed; Step 4: Use the mixed powder of chlorinated polyvinyl chloride and polytetrafluoroethylene to perform high temperature chemical purification on the material.

[0020] Preferably, the mass ratio of the chopped carbon fiber to the powdered resin is 100:(10-50).

[0021] Preferably, in step 2, the heating curing system is 100°C / 1h-150°C / 2h-200°C / 2h, and the heating rate is 100-200°C / h.

[0022] Preferably, in step 3, the temperature of high-temperature carbonization and graphitization is 2000°C-3000°C, and the heating rate is 100-200°C / h; the curing rotation rate is 1-5 revolutions / minute.

[0023] Preferably, in step 4, the purification material is chlorinated polyvinyl chloride powder and polytetrafluoroethylene powder, the mass ratio of which is (100-300):100, and the amount used is 10-50 times the mass of the impurities.

[0024] Preferably, in step 4, the transfer rate of the purified material is 10 g / min-50 g / min; the purification temperature is 2000°C-2600°C.

[0025] Preferably, the powdered resin is solid phenolic resin powder or solid asphalt powder, with a powder size of 10-50 μm, a solid content of >97%, a fluidity of 20-30 mm, a polymerization speed of 50-90 s (150° C.), and a residual carbon content of 50-60%.

[0026] Preferably, the carbon fiber cloth is of T300 grade, with a gram weight of >200g / m 2 , the thickness of high-density carbon fiber / carbon composite material sheet is ≥10 mm, the tensile strength is >100 MPa, and the bending strength is >100 MPa.

[0027] The high-purity, low-thermal-conductivity, low-density carbon fiber / carbon composite thermal field material prepared by the present invention has the following characteristics: 1. Fiber distribution is uniform and density is low: density ≤ 0.16 ± 0.01 g / cm³; 2. High temperature resistance: suitable for silicon carbide crystal growth at 2300℃.

[0028] 3. High purity: impurity content is less than ≤1.2 ppm.

[0029] 4. Low thermal conductivity: thermal conductivity ≤ 0.20 W / (m·K).

[0030] 5. Low conductivity: conductivity ≤4.0 S / cm, avoiding electromagnetic self-heating.

[0031] 6. Environmental protection: no solvent used, no pollution.

[0032] 7. High efficiency and low energy consumption: the preparation process is fast and energy-saving.

[0033] Application Advantages 1. Excellent thermal insulation performance: In the silicon carbide crystal growth furnace, the power is ≤14 kW at 2300℃, showing good thermal insulation performance.

[0034] 2. High heating stability: The power is stable in the high temperature stage, which is suitable for thermal field applications of third-generation semiconductor materials.

[0035] 3. Simple and efficient process: No solvent is required in the preparation process, which shortens the process time and reduces energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is an example of the microscopic morphology of the high-purity, low-thermal-conductivity, low-density carbon fiber / carbon material prepared in Example 1 of the present invention, wherein: Figure 1 Figure a1 in Figure 1 Figure a2 in the figure is the XY surface diagram of the carbon fiber / carbon composite thermal field material magnified 200 times and 500 times respectively; Figure 1 Figure b1 in Figure 1 Figure b2 in the figure is the XZ surface image of the carbon fiber / carbon composite thermal field material magnified 200 times and 500 times respectively.

[0037] Figure 2The high-purity, low-thermal-conductivity, low-density carbon fiber / carbon composite thermal field material (0.16 g / cm 3 ) Real-time power consumption diagram for application in a SiC crystal growth furnace. DETAILED DESCRIPTION

[0038] Example 1 Objective: To prepare high-purity, low-thermal-conductivity, low-density carbon fiber / carbon composite thermal field materials with a density of 0.16 g / cm³.

[0039] Preparation steps S1, Short-cut carbon fiber high-speed shear dry dispersion Use short-cut viscose-based carbon fibers (length 3 mm) and add them into a high-speed shear disperser. The shear blade speed is 3000 rpm and stirred for 5 minutes.

[0040] Powdered phenolic resin (the mass ratio of carbon fiber to resin is 3:1) was added and stirring was continued for 5 minutes to form a fluffy and dispersed chopped carbon fiber / phenolic resin system.

[0041] S2, Rotary Pressing and Curing The dispersed system is pressed into a metal mold under a pressure of 100 tons. After the mold is locked, it is placed on a rotating bracket in a heating oven and rotated at a speed of 3 revolutions per minute for curing.

[0042] Curing system: 100℃ / 1h → 150℃ / 2h → 200℃ / 2h, heating rate 150℃ / h.

[0043] S3, high temperature carbonization and graphitization Wrap it with a layer of T300 carbon fiber cloth (weight 200 g / m²) and then fix it with a high-density perforated carbon fiber / carbon composite material sheet (tensile strength 160 MPa, bending strength 120 MPa, thickness 10 mm).

[0044] Carbonization and graphitization are carried out in a high temperature furnace, and the process conditions are: 350℃ / 1h → 800℃ / 1h → 1300℃ / 1h → 1800℃ / 1h → 2400℃ / 1h → 2600℃ / 1h.

[0045] 4. High temperature chemical purification A mixed powder of chlorinated polyvinyl chloride and polytetrafluoroethylene (mass ratio 100:100) was used, the amount of purified powder was 50 times the impurity content, and the feed rate was 50 g / min.

[0046] Chlorinated polyvinyl chloride: chlorine content 60%, particle size 40 microns; polytetrafluoroethylene: particle size 10 microns.

[0047] Purification temperature 2200℃.

[0048] result: Density: 0.16±0.01 g / cm³ Impurity content: 1.2 ppm Conductivity: 4.0 S / cm 1500℃ Thermal conductivity: 0.40 W / (m·K) 2300℃ Power: 14 kW Operating temperature: >2300℃ Example 2

[0049] Goal: To adjust the purification process to produce a material with a density of 0.18 g / cm³.

[0050] Adjustment content Step S4: The amount of purified powder used is 30 times the impurity content, and the feeding speed is 30 g / min.

[0051] result: Density: 0.18±0.01 g / cm³ Impurity content: 8 ppm Conductivity: 4.8 S / cm 1500℃ Thermal conductivity: 0.45 W / (m·K) 2300℃ Power: 14.3 kW Operating temperature: >2300℃ Example 3

[0052] Goal: To further adjust the purification process and produce a material with a density of 0.20 g / cm³.

[0053] Adjustment content Step S4: The amount of purified powder used is 10 times the impurity content, and the feeding speed is 10 g / min.

[0054] result: Density: 0.20±0.01 g / cm³ Impurity content: 17 ppm Conductivity: 5.7 S / cm 1500℃ Thermal conductivity: 0.46 W / (m·K) 2300℃ Power: 14.8 kW Operating temperature: >2300℃ Comparative Example 1 Adjustments: Step S1: impregnation with liquid phenolic resin.

[0055] Step S2: No rotation curing is performed.

[0056] question: Wet forming results in high energy consumption and increased time for drying.

[0057] Production efficiency is reduced and there is liquid contamination.

[0058] The glue flow phenomenon is serious, the density deviation is large, and the product is unqualified.

[0059] Comparative Example 2 Adjustments: Step S3: directly placing the carbon fiber cloth and the perforated carbon fiber / carbon composite material plate on a high temperature furnace support without fixing the carbon fiber cloth and the perforated carbon fiber / carbon composite material plate.

[0060] question: The product cracks during the carbonization and graphitization process and becomes scrapped.

[0061] Comparative Example 3 Adjustments: Step S4 high temperature chemical purification is not performed.

[0062] question: The impurity content is high (300 ppm) and cannot be used in the semiconductor field.

[0063] Summary 1. Embodiment 1-3: By optimizing the amount of purified powder and the feed rate, high-purity, low-thermal-conductivity, and low-density carbon fiber / carbon composite thermal field materials with different densities were successfully prepared.

[0064] The material has excellent performance and is suitable for high temperature thermal field applications.

[0065] 2. Comparative example: Liquid phase impregnation and non-rotational solidification lead to problems such as increased energy consumption, pollution, glue flow, and large density deviation.

[0066] Failure to use a fixed structure or to perform purification can result in a product that cracks or has impurities too high to meet application requirements.

[0067] The present invention solves the problems of uneven dispersion, high energy consumption, and severe pollution in the prior art by optimizing the preparation process, and significantly improves the material performance and application scope.

[0068] Test results.

[0069] .

Claims

1. A high-purity, low-thermal-conductivity, low-density carbon fiber / carbon composite thermal field material, characterized in that: The material has the following properties: Density: ≤0.2±0.01 g / cm³; Impurity element content: ≤17ppm; Conductivity: ≤5.7 S / cm.

2. The high-purity, low-thermal-conductivity, low-density carbon fiber / carbon composite thermal field material according to claim 1, characterized in that: The material has the following properties: 1500℃ thermal conductivity: ≤0.46 W / (m·K); Power in a 6-inch SiC crystal growth furnace at 2300°C: ≤14.8 kW.

3. The method for preparing the high-purity, low-thermal-conductivity, low-density carbon fiber / carbon composite thermal field material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: Step 1: Dispersing the powdered resin material and the chopped carbon fiber by high-speed shear dry method; Step 2: heat and solidify the mold by rotating, pressing and heating; Step 3: After fixing with carbon fiber cloth and high-density perforated carbon fiber / carbon composite material sheet, high-temperature carbonization and graphitization are performed; Step 4: Use the mixed powder of chlorinated polyvinyl chloride and polytetrafluoroethylene to perform high temperature chemical purification on the material.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the chopped carbon fiber to the powdered resin is 100:(10-50).

5. The preparation method according to claim 3, characterized in that: In step 2, the heating curing system is 100 ℃ / 1h-150 ℃ / 2h-200 ℃ / 2h, and the heating rate is 100-200 ℃ / h.

6. The preparation method according to claim 3, characterized in that: In step 3, the temperature of high-temperature carbonization and graphitization is 2000°C-3000°C, and the heating rate is 100-200°C / h; the curing rotation rate is 1-5 revolutions / minute.

7. The preparation method according to claim 3, characterized in that: In step 4, the purification material is chlorinated polyvinyl chloride powder and polytetrafluoroethylene powder, the mass ratio of which is (100-300):100, and the amount used is 10-50 times the mass of the impurities.

8. The preparation method according to claim 3, characterized in that: In step 4, the transfer rate of the purified material is: 10 g / min-50 g / min; the purification temperature is: 2000°C-2600°C.

9. The preparation method according to claim 3, characterized in that: The powdered resin is solid phenolic resin powder or solid asphalt powder, with a powder size of 10-50 μm, a solid content of >97%, a fluidity of 20-30 mm, a polymerization speed of 50-90 s (150° C.), and a residual carbon content of 50-60%.

10. The preparation method according to claim 3, characterized in that: The carbon fiber cloth is T300 grade, with a gram weight of >200g / m 2 , the thickness of high-density carbon fiber / carbon composite material sheet is ≥10 mm, the tensile strength is >100 MPa, and the bending strength is >100 MPa.

Citation Information

Patent Citations

  • Carbon-containing refractory and process for producing the same

    CA2212726A1

  • Heat insulation wall integral pouring material and construction method

    CN101376582A

  • Heat insulating material and preparation method thereof

    CN103373014A

  • Pitch-based carbon fiber non-woven felt heat-insulating cylinder and preparation method thereof

    CN104261853A

  • An electrochemical process for preparing a compound comprising a metal or metalloid and a peroxide, ionic or radical species

    CN107532309A